Morphometry-Based Identification of Snail Host Species for Helminth Parasites in Chitwan, Nepal - Pathak, Chet Raj (Journal of the Institute of Agriculture and Animal Science, 2025)
Snails serve as intermediate hosts for numerous parasitic diseases of humans and animals. This study examined the morphometry-based identification for ten snail species from terrestrial and aquatic habitats in Chitwan, Nepal. In total, 120 snails were identified based on regional taxonomic keys. Morphometric analysis showed interspecific variation in shell dimensions among the studied snails. Lissachatina fulica exhibited the largest size with an ovo-conical shell (61.33 ± 2.96 mm height; 31.58 ± 3.59 mm width), while Indoplanorbis exustus represented the smallest species (12.33 ± 1.93 mm height; 5.38 ± 0.68 mm width). Ovate lymnaea showed moderate size (18.45 ± 1.48 mm height; 8.95 ± 2.99 mm width), whereas Bellamya dissimilis had a larger conical form (26.67 ± 1.69 mm × 20.25 ± 1.21 mm). Discoidal Macrochlamys indica and elongate-conical species (Brotia costula, Thiara scabra, Melanoides tuberculata) exhibited distinct height-to-width ratios, reflecting habitat-specific adaptations. Globose taxa such as Pila globosa (29.50 ± 11.30 mm × 26.83 ± 9.97 mm) and Cyclophorus sp. (24.25 ± 1.64 mm × 30.17 ± 1.86 mm) showed broader shells relative to height. Aperture dimensions were widest in L. fulica (34.58 ± 2.93 mm × 20.42 ± 0.36 mm) and the narrowest in T. scabra (4.92 ± 0.95 mm × 2.38 ± 0.36 mm). These morphometric variations not only reflect ecological adaptations, but also highlight the epidemiological importance of snails as intermediate hosts of human and animal health significant parasites, such as Schistosoma, Fasciola, and Angiostrongylus species.